Continuous production of cephalosporin-C by immobilized microbial cells using symbiotic mode in a packed bed bioreactor - Kundu S.; Mahapatra A.C.; KumarNigam V.; Kundu K. (My University, 2025)
Cephalosporins are usually produced semisynthetically from Cephalosporin-C, which is exclusively produced by Cephalosporium acremonium. Free cell studies for the production of Cephalosporin-C had some limitation such as pulpy growth of fungus causing an appreciable rise in the broth viscosity affecting the transfer of oxygen and other nutrients into the cells. High cell concentrations cannot be maintained because of wash out phenomenon at high dilution rates. The whole cell immobilization technique is a potentially important process for Cephalosporin-C biosynthesis, where increase cell densities were maintained and broth-handling problems were reduced. Cephalosporin-C fermentation is a highly aerobic process. The symbiotic relationship of Cephalosporium acremonium and Chlorella pyrenoidosa has been used to increase oxygen transfer rate to the fungi by co-immobilizing it with algae. Co immobilization of whole cells of fungus and algae were carried out in different immobilizing agents and the systems were coated with polyacrylamide resin of pharmaceutical grade to overcome the problems of leakage. The operational stability of immobilized systems in a packed bed reactor was also studied.